Syngas-Enriched hydrogen production via catalytic gasification of water hyacinth using renewable palm kernel shell hydrochar - April Chee, Ling Kwang; Bridgid Chin, Lai Fui; Shaharin Anwar, Sulaiman; Chai, Yee Ho; Agus, Saptoro; Hadiza Aminu, Umar; Serene Lock, Sow Mun; Yiin, Chung Loong (Elsevier Ltd., 2024)
Syngas produced from biomass gasification has emerged as a highly promising substitute for conventional fossil fuel, catering to various industrial applications while ensuring minimal greenhouse gas emissions. Water hyacinth (WH) has been a major concern due to its invasive nature and uncontrollable growth which impedes aquatic growth and urban management. Fortunately, WH is a potential biomass feedstock due to the comparable cellulose and hemicellulose contents alongside high carbon content and high calorific value which reflects good biofuel properties. Therefore, this study aims to investigate the conversion of WH biomass via catalytic air gasification for syngas-enriched hydrogen production using palm kernel shell hydrochar (PKSH). A parametric study was conducted in a lab-scale fixed-bed downdraft gasifier based on the response surface methodology coupled with Box-Behnken design (RSM-BBD). The combined interaction effects of the influencing parameters investigated are temperature (600–800 °C), biomass particle size (2–6 mm), catalyst loading (0–10 wt%), and air flow rate (1–3 L/min). Temperature was revealed to be the primary factor with significant influence on the H2 and CO output. Maximum syngas (30.09 vol%) compositions of 11.14 vol% H2 and 18.95 vol% CO were obtained at 800 °C with a particle size of 6 mm and air flow rate of 2 L/min alongside 5 wt% PKSH catalyst loading.